2005
DOI: 10.1186/1472-6955-4-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long-term total parenteral nutrition on gut mucosal immunity in children with short bowel syndrome: a systematic review

Abstract: Background: Short bowel syndrome (SBS) is defined as the malabsorptive state that often follows massive resection of the small intestine. Most cases originate in the newborn period and result from congenital anomalies. It is associated with a high morbidity, is potentially lethal and often requires months, sometimes years, in the hospital and home on total parenteral nutrition (TPN). Long-term survival without parenteral nutrition depends upon establishing enteral nutrition and the process of intestinal adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 154 publications
1
36
0
2
Order By: Relevance
“…There is no direct evidence in human models that TPN promotes bacterial overgrowth, impairs neutrophil functions, inhibits blood's bactericidal effect, or causes villous atrophy. Thus TPN may be more expensive than EN, but it does not seem to be less safe [8]. It is probably the lack of EN rather than reduced GI immunity or the absolute caloric intake that is responsible for many of the adverse effects of TPN such as induction of villus atrophy, epithelial cell apoptosis, and increasing of mucosal permeability [9].…”
Section: Deprivation Of Enteral Nutritionmentioning
confidence: 99%
“…There is no direct evidence in human models that TPN promotes bacterial overgrowth, impairs neutrophil functions, inhibits blood's bactericidal effect, or causes villous atrophy. Thus TPN may be more expensive than EN, but it does not seem to be less safe [8]. It is probably the lack of EN rather than reduced GI immunity or the absolute caloric intake that is responsible for many of the adverse effects of TPN such as induction of villus atrophy, epithelial cell apoptosis, and increasing of mucosal permeability [9].…”
Section: Deprivation Of Enteral Nutritionmentioning
confidence: 99%
“…On the other hand, gutassociated lymphoid tissue (GALT) plays a critical role in the maintenance of gut structures, function, metabolism, and immunity [16]. It has been shown that glutamine supplementation protects the GALT atrophy and IgA depletion that result from long-term TPN and enhances nutrient absorption [17,18].…”
Section: Some Trophic Factors (Ie Growth Hormone [Gh] Insulinlike mentioning
confidence: 99%
“…Following massive SBR the intestine hypertrophies, and nutrient absorption becomes more efficient (Duran 2005). The intestine lengthens, and the diameter and villus height increase with a resultant increase in surface area (Duran 2005).…”
Section: Introductionmentioning
confidence: 99%